A Mixed-Methods Investigation into Patients' Decisions to Attend an Emergency Department for Chronic Pain. Issue 10 (19th March 2021) - Brady, Bernadette; Andary, Toni; Pang, Sheng Min; Dennis, Sarah; Liamputtong, Pranee; Boland, Robert; Tcharkhedian, Elise; Jennings, Matthew; Pavlovic, Natalie; Zind, Marguerite; Middleton, Paul; Chipchase, Lucy
Abstract: Objective: This study explored factors that underpin decisions to seek emergency department (ED) care for chronic noncancer pain in patients identifying as culturally and linguistically diverse (CALD) or Australian born. Design and Methods: This mixed-methods study was underpinned by the Behavioral Model of Health Services Use conceptual framework. Consenting consecutive patients attending the ED for a chronic pain condition were recruited to a CALD (n = 45) or Australian-born (n = 45) cohort. Statistical comparisons compared the demographic, pain, health literacy, and episode of care profiles of both cohorts. Twenty-three CALD and 16 Australian-born participants consented to an audio-recorded semi-structured interview (n = 24) or focus group (n = 5 focus groups) conducted in their preferred language. Interviews were translated and transcribed into English for analysis using applied thematic analysis, guided by the conceptual framework. Data were triangulated to investigate the patterns of ED utilization and contributing factors for both cohorts. Results: ED attendance was a product of escalating distress, influenced by the degree to which participants' perceived needs outweighed their capacity to manage their pain. This interaction was amplified by the presence of predisposing factors, including constrained social positions, trauma exposure, and biomedical health beliefs. Importantly, experiences varied between the two cohorts with higher degrees of pain catastrophizing, lower health literacy, and greater social challenges present for the CALD cohort. Conclusion: This study highlights the role contextual factors play in amplifying pain-related distress for CALD and Australian-born patients with chronic pain. The findings support a need for health care providers to recognize features of higher vulnerability and consider streamlining access to available support services.